Association Association of genetic variant of OXTR (rs53576) and MTNR-1B (rs10830963 and rs1387153) with symptoms of stress in Pakistani women with Gestational Diabetes. - Abid, Fatima; Ahmed , Sadaf; Fatima, Syeda Sadia; Noushad , Shamoon (International Journal of Endorsing Health Science Research, 2021)
Background: Pregnancy continues to be an event full of risks, complications and adverse outcomes for women despite advanced clinical and diagnostic methods and treatment options available in medicine. Diabetes, as a multifactorial and complex disease, is a possible outcome of a blend of numerous genetic variants of differing scarcities. The exact etiology of gestational diabetes mellitus (GDM) is unclear; however, the interaction of genetic and environmental factors, especially the genetic variants identified as the genetic loci for type 2 diabetes as candidate genes for GDM. Methodology: It will be a case-control study with a genetic analysis of single nucleotide polymorphisms (SNPs) of candidate genes expressed using real-time PCR with sequencing. The study will also evaluate the primer sequence of SNPs. Discussion: We will be able to share the findings after the completion of our research. The results of this study will able helpful in addressing the psycho-physiological needs of women with GDM, which may also be used to devise strategies to benefit the sustainable long-term behavioural change following the affected pregnancy.